A Targeted Management of the Nutrient Solution in a Soilless Tomato Crop According to Plant Needs - Signore, Angelo; Serio, Francesco; Santamaria, Pietro (Frontiers in Plant Science, 2016)
The adoption of closed soilless systems is useful in minimizing the environmental impact of the greenhouse crops. Instead, a significant problem in closed soilless systems is represented by the accumulation of ions in the recycled nutrient solution, in particular the unabsorbed or poorly absorbed ones. To overcome such problem, we: 1) studied the effect of several values of the electrical conductivity (EC) of nutrient solution in a NFT (Nutrient Film Technique) system on a cherry type tomato crop, and 2) define a NS (called recovery solution), based on the concept of “uptake concentration” and transpiration-biomass ratio, that fits the real needs of the plant with respect to water and nutrients. Three levels of EC set point (SP), above which the NS was completely replaced (SP5, SP7.5, and SP10 for the EC limit of 5, 7.5 and 10 dS m-1, respectively), were established. The SP10 treatment yield was not different from other treatments, and it allowed a better quality of the berries (for dry matter and total soluble solids) and higher environmental sustainability due to a lower discharge of total nutrients into the environment (37 and 59% with respect to SP7.5 and SP5, respectively).The recovery solution used in the second trial allowed a more punctual NS management, by adapting to the real needs of the crop. Moreover, it allowed a lesser amount of water and nutrients to be discharged into the environment and a better use of brackish water, due to a more accurate management of the EC of the NS. The targeted management, based on transpiration-biomass ratio, indicates that, in some stages of the plant cycle, the nutrient solution used can be diluted, in order to save water and nutrients. With such management a closed cycle can be realized without affecting the yield, but improving the quality of the tomato berries.